Receptor-like Kinase GOM1 Regulates Glume-Opening in Rice - Xinhui Zhao; Mengyi Wei; Qianying Tang; Lei Tang; Jun Fu; Kai Wang; Yanbiao Zhou; Yuanzhu Yang (Plants)
Glume-opening of thermosensitive genic male sterile (TGMS) rice (Oryza sativa L.) lines after anthesis is a serious problem that significantly reduces the yield and quality of hybrid seeds. However, the molecular mechanisms regulating the opening and closing of rice glumes remain largely unclear. In this study, we report the isolation and functional characterization of a glum-opening mutant after anthesis, named gom1. gom1 exhibits dysfunctional lodicules that lead to open glumes following anthesis. Map-based cloning and subsequent complementation tests confirmed that GOM1 encodes a receptor-like kinase (RLK). GOM1 was expressed in nearly all floral tissues, with the highest expression in the lodicule. Loss-of-function of GOM1 resulted in a decrease in the expression of genes related to JA biosynthesis, JA signaling, and sugar transport. Compared with LK638S, the JA content in the gom1 mutant was significantly reduced, while the soluble sugar, sucrose, glucose, and fructose contents were significantly increased in lodicules after anthesis. Together, we speculated that GOM1 regulates carbohydrate transport in lodicules during anthesis through JA and JA signaling, maintaining a higher osmolality in lodicules after anthesis, which leads to glum-opening.